Bilateral internal thoracic artery grafting in robotic beating-heart totally endoscopic coronary artery bypass: 10-year outcomes - Nisivaco, Sarah; Bhasin, Riya; Kitahara, Hiroto; Patel, Brooke; Coleman, Charocka; Grady, Kaitlyn; Oh, Won Hee; Balkhy, Husam H. (Annals of Cardiothoracic Surgery; Vol 13, No 4 (July 31, 2024): Robotic Coronary Artery Bypass Grafting I, 2024)
Background: Multi-arterial grafting (MAG) with bilateral internal thoracic arteries (BITAs) is superior to single internal thoracic artery (ITA) and veins, however, sternal wound infection (SWI) is a deterrent to using BITA, especially in diabetic and obese patients. Sternal-sparing approaches, including robotic totally endoscopic coronary artery bypass (TECAB), may mitigate this risk. We reviewed outcomes of robotic TECAB with BITA grafting. Methods: A total of 871 patients underwent robotic TECAB at our institution from 7/2013 to 4/2024. Of these, 406 patients received BITA grafts and are the subject of this review. Early and mid-term clinical outcomes were reviewed and angiographic patency in those undergoing hybrid revascularization with percutaneous coronary intervention (PCI) after TECAB. All cases were performed via a beating-heart robotic approach, with standard TECAB port placement. Results: The mean age of the cohort was 67±9 years and 16% were female. The mean Society of Thoracic Surgeons (STS) risk was 1.47%±2.2%. Thirty-nine percent were diabetic (15% insulin-dependent) and 39% had a body mass index (BMI) ≥30 kg/m2. Twenty percent had an ejection fraction (EF) ≤40%. Ninety-eight percent of cases were completed off-pump and there were no conversions to sternotomy. The mean number of grafts per patient was 2.2±0.4. The mean intensive care unit (ICU) and hospital length of stay (LOS) were 1.22±0.62 and 2.44±0.83 days, respectively. Postoperative complications included atrial fibrillation in 13%, acute kidney injury (AKI) in 3.4%, return to theatre for bleeding in 0.7%, postoperative myocardial infarction (MI) in 0.2%, and stroke in 0.2%. Thirty-day mortality was 1.2% [observed/expected (O/E): 0.89]. Return to full activities and work occurred at mean of 14±8.6 and 17±13 days, respectively. Two hundred and two patients (50%) had ‘advanced’ hybrid revascularization (with at least two arterial grafts and stents). ITA early graft patency in this cohort of patients was 271/278 (98%) with 100% left ITA to left anterior descending artery (LITA-LAD) patency. Mid-term follow-up was complete in all patients at mean of 51±36 months (longest follow-up at 10 years). All-cause mortality was 13% and cardiac-mortality was 2.5%. Freedom from angina was 96%, and freedom from repeat revascularization was 94%. Conclusions: Use of the beating-heart robotic TECAB approach facilitates BITA grafting to achieve multi-vessel arterial revascularization of the left coronary system, with excellent 10-year outcomes.